Pengaruh Kualitas Layanan Sirkulasi terhadap Minat Kunjung Pemustaka di Dinas Perpustakaan dan Arsip Daerah Kabupaten Bungo Provinsi Jambi - Hafifahreza, Riskia; Nurizzati, Nurizzati (Scinary, 2024)
The purpose of this research is to describe the effect of circulation service quality on library visitors interest at Dinas Perpustakaan dan Arsip Daerah Kabupaten Bungo Provinsi Jambi. This study uses a quantitative descriptive method, with the population consisting of library members of Dinas Perpustakaan dan Arsip Daerah Kabupaten Bungo Provinsi Jambi, and the sample is 70 people. The data were analyzed using normality test, pearson product moment, partial test (t-test) and coefficient of determination test. Based on the results, it can be concluded that circulation service quality has aneffect on the interest in visiting at Dinas Perpustakaan dan Arsip Daerah Kabupaten Bungo Provinsi Jambi. The hypothesis test shows a significance value of 0,000 < 0,05, indicating that the variable X (circulation service) has an effect on variable Y (visitior interest)